Artificial Diet Influences Population Growth of the Root Maggot Bradysia impatiens (Diptera: Sciaridae). Issue 5 (19th October 2020) - Gou, Yuping; Quandahor, Peter; Zhang, Kexin; Guo, Sufan; Zhang, Qiangyan; Liu, Changzhong; Coulter, Jeffrey A
Abstract: In order to investigate the effects of artificial diets on the population growth of root maggot Bradysia impatiens, its population growth parameters were assayed on eight artificial diets (Diet 1, D2, D3, D4, D5, D6, D7, and D8). Results showed that developmental duration from egg to pupa was successfully completed on all eight artificial diets. However, the egg to pupal duration was shortest, while the survival rate of four insect stages was lowest when B. impatiens was reared on D1. When B. impatiens was reared on D7 and D8, the survival rate, female longevity, and female oviposition were higher than those reared on other diets. When B. impatiens was reared on D7, the intrinsic rate of increase ( r m = 0.19/d), net reproductive rate ( R 0 = 39.88 offspring per individual), and finite rate of increase (λ = 1.21/d) were higher for its population growth with shorter generation time ( T = 19.49 d) and doubling time ( Dt = 3.67 d). The findings indicate that the D7 artificial diet is more appropriate for the biological parameters of B. impatiens and can be used an indoor breeding food for population expansion as well as further research. We propose that vitamin C supplement added to the D7 is critical for the improvement of the B. impatiens growth.